Pronatalist policies' backlash in authoritarian regimes - Thomas Baudin; Robert Stelter (University of Basel, Center of Business and Economics (WWZ), 2024)
European fascist regimes have attached great importance to nationalistic families and designed policies to perpetuate them. Most offered policy packages with interest-free loans repayable through childbirth, along with allowances and tax deductions for large families. Using a difference-in-difference approach and Nazi Germany as a case study, we show that these policies may have counterproductive effects due to negative selection mechanisms in the marriage market. The excessive pressure to marry exerted on singles results in lower quality, ultimately less fertile, and more fragile unions. This finding is important as the main European far-right parties today propose reinstating these policy packages.
Keywords: N3; D1; J1; 330; Family policies; Fascism and Nazism; Fertility; Marriage; Divorce; Female labor force participation